Photoelectroactivity of Bismuth Vanadate Prepared by Combustion Synthesis: Effect of Different Fuels and Surfactants - Afonso, Renata; Serafim, Jessica A.; Lucilha, Adriana C.; Silva, Marcelo R. [UNESP]; Lepre, Luiz F.; Ando, Romulo A.; Dall'Antonia, Luiz H. (Soc Brasileira Quimica, 2014)
The bismuth vanadate (BiVO4) is a semiconductor that has attracted much attention due to the photocatalytic efficiency in the visible light region. The objective of this work was to synthesize monoclinic BiVO4 by solution combustion synthesis, with different surfactants and fuels and apply it as photoelectrodes. The characterization by infrared spectroscopy and Raman spectroscopy showed that all samples showed characteristic bands of the monoclinic structure BiVO4. The samples synthesized with glycine and glycine/Tween (R) 80 had V2O5. The film obtained from the alanine/Tween (R) 80 showed highest photocurrent values, which may be related to smaller size particles (200 to 300 nm) observed by scanning electron microscopy images. The films obtained using alanine showed highest values of rate constant reaction and percentage discoloration of methylene blue.
Keywords: BiVO4; photoelectrocatalysis; electrophoretic deposition; alanine